DETERMINAN KEPUTUSAN INVESTASI GENERASI Z - Retno Endah Supeni; Yusron Rozzaid; Maheni Ika Sari (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2023)
Generation Z has a great potential as part of the increasingly diverse consumption and investment targets in the current era of information technology advancement. Their important role in the economy must be directed to be wise in managing personal finances. The purpose of the study was to examine impact of income, financial literacy, and financial behavior toward the investment decisions of the Z generation. Observations in this study were 562 respondents from active students at the Faculty of Economics and Business, Universitas Muhammadiyah Jember. Multiple linear regression analysis was used as a data analysis tool. The results of the study show that income has no significant effect on investment decisions, while financial literacy and financial behavior are found to have a significant effect on investment decisions